Prohibition on making a will in electronic form under the legislation of the Republic of Kazakhstan: problems and ways to solve them - Zhetibayev, Zh.K. (Bulletin of the Karaganda University “Law Series”, 2021)
The article is devoted to the consideration of issues related to the making of a will in electronic form under the civil legislation of the Republic of Kazakhstan. The author gives a general description of making a will according to the legislation of the Republic of Kazakhstan. Special attention is drawn to the experience of foreign countries, which demonstrates the legal consolidation of a will in electronic form, as well as the difficulties that arise during their implementation (especially aspects related to the storage of such a will and the identification of the person who made it). In addition, the analysis of law enforcement practice on this issue and the application of the rule on a harmless error by the countries of the Anglo-Saxon legal family is given. During the research the author reveals the positive and negative aspects of making a will in electronic form. However, the conducted research allows the author to justify the inexpediency of allowing of making a will in electronic form at the legal level, therefore, an edition of the provision is proposed that would establish a direct ban on this action in the civil legislation of the Republic of Kazakhstan. This proposal is justified by the presence of quite serious difficulties in practice related to the legal and technical side of an electronic will, as well as the fact that the legalization of making a will in electronic form can contribute to the increase in abuse of civil law subjects of their rights, as well as fraud and cybercrime. The conclusions made by the author in the course of this study can be used as a basis for the development of amendments to the current legislation.